The Validity and Reliability of the Turkish Version of the Attitudes to Fer-tility and Childbearing Scale (AFCS) - Pınar Sercekus; Erkan Alataş; Sinem Göral; Sevgi Özkan (International Journal of Assessment Tools in Education, 2021)
This study, a descriptive and methodological type of research, was conducted to evaluate the validity and reliability of the Turkish adaptation of the Attitudes to Fertility and Childbearing Scale (AFCS), developed by Söderberg et al. (2015). The sample of this study consisted of 224 women who had not given birth yet and who were between the ages of 20-30. The scale is a Likert-type measuring instrument consisting of 21 items, in three dimensions. Internal consistency analyses were conducted to determine its reliability. After confirming the linguistic validity, expert opinions were obtained for the content validity. Furthermore, the Item Content Validity Index (I-CVI) and the Scale Content Validity Index (S-CVI) were used to assess its content validity. The construct validity was performed using confirmatory factor analysis. As a result of the confirmatory factor analysis carried out for the construct validity, a three-factor structure of the scale was found to have a good level of model fitness indices (RMSEA=.067, SRMR=.075, CFI=.96). As a result of the scale reliability analysis, the internal consistency coefficient was found to be .82 for the total scale and internal consistency reliability coefficients of the sub-scales were found to be .93 for the "importance of fertility for the future" sub-scale, .87 for the "childbearing as a hindrance at present" sub-scale, and .81 for the "social identity" sub-scale. AFCS is a valid and reliable measurement tool that can be used to measure the fertility and childbearing attitudes of women in a fertile age.